Dampak Wisata Taman Ghanjaran Terhadap Pendapatan Masyarakat Desa Ketapanrame Kabupaten Mojokerto - Febriansyah, Galvin Arfendo; Nuraini, Ida (JOURNAL OF ECONOMIC AND SOCIAL EMPOWERMENT, 2022)
Economics is a field of study on the management of individual, community and state material resources to improve the welfare of human life. Meanwhile, community income is the receipt of remuneration or salary from business results obtained by individuals or groups of households within a certain period of time. For Indonesia, the tourism sector plays an important role in the national economy, both as a source of foreign exchange earners and as a creator of employment and business opportunities. In addition, tourism also has a very important role in development, namely encouraging regional development, increasing national income in order to improve the welfare and prosperity of the people and fostering a sense of love for the homeland, enriching national culture and strengthening its development in order to strengthen national identity and strengthen friendship between nations. This type of research is descriptive quantitative research. The data used in this study were interviews and questionnaires. The sample used was 52 respondents. The research method used to measure income before and after is using the Paired Sample t-Test difference test.The influence of tourism on the income of the people of the village of Ketapanrame shows significant results. The results showed that the influence of Ghanjran Park tourism on increasing people's income was quite effective. This means that there is an increase in people's income after the Ghanjaran park tour than before the Ghanjaran park tour.